From Fisheries Constraints to Marine Tourism Revenue: Evidence from Konawe Kepulauan - Syahril Syahril; Marsan Julianto; Saiful Agusta Torada (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study explains why marine tourism has become a more realistic source of local own-source revenue than fisheries in Konawe Kepulauan, Indonesia, despite the regency's strong maritime resource base. A qualitative case-study design combined interviews with the Regional Finance Agency, Tourism Office, and Fisheries Office with documentary analysis of retribution, visitor, and regulatory data. Fisheries remain central to coastal livelihoods but are weakly connected to local fiscal capture because of constrained district authority, transfer of fish auction-site management to the provincial level, limited chargeable public facilities, and the predominance of small-scale fishers. Marine tourism offers clearer retribution objects through Pantai Kampa and Air Terjun Tumburano, including entrance tickets, parking, gazebo rental, and related services. Tourism retribution rose from IDR 21.128 million in 2022 to IDR 30.530 million in 2025 and reached IDR 35.310 million by May 2026, while visitor arrivals increased from 5,060 in 2025 to 7,308. The proposed Maritime Fiscal Transition Model explains the shift from resource-based maritime potential to service-based tourism revenue while retaining fisheries as a livelihood pillar. The findings support a dual strategy combining fisheries strengthening with accountable, community-supported, and sustainable marine tourism development.